More or Less Pluralistic? A Typology of Remedial and Alternative Perspectives on the Monetary Valuation of the Environment. (1st June 2014) - Lo, Alex Y.
Abstract : Maintaining plural values is important when there is no conclusive principle by which the relative priority of normative positions can be determined. Value-articulating institutions predicated upon such principles have a low pluralistic potential. In response to the failures of stated-preference approaches to economic valuation, new perspectives have been developed to capture plural values. Three broad approaches are identified. The first, functional diversification, seeks to encompass the multiple qualities of the object of valuation, whereas positional modification enforces a particular mode of thinking on the subject. Both entail a prior judgement of values and benefit from a reduction in the range of values. Eventually, therefore, both approaches collapse pluralism to a problem that can be tackled. The third approach, structural reconstruction, has greater pluralistic potential, recognising that the more diverse and uncertain the object of valuation, the more compelling it is.